Increased mast cell numbers in a calcaneal tendon overuse model. Issue 6 (25th July 2013) - Pingel, J.; Wienecke, J.; Kongsgaard, M.; Behzad, H.; Abraham, T.; Langberg, H.; Scott, A.
<x xml:space="preserve">Abstract</x> Tendinopathy is often discovered late because the initial development of tendon pathology is asymptomatic. The aim of this study was to examine the potential role of mast cell involvement in early tendinopathy using a high‐intensity uphill running (HIUR) exercise model. Twenty‐four male Wistar rats were divided in two groups: running group (n = 12); sedentary control group (n = 12). The running‐group was exposed to the HIUR exercise protocol for 7 weeks. The calcaneal tendons of both hind limbs were dissected. The right tendon was used for histologic analysis using Bonar score, immunohistochemistry, and second harmonic generation microscopy (SHGM). The left tendon was used for quantitative polymerase chain reaction (qPCR) analysis. An increased tendon cell density in the runners were observed compared to the controls (P = 0.05). Further, the intensity of immunostaining of protein kinase B, P = 0.03; 2.75 ± 0.54 vs 1.17 ± 0.53, was increased in the runners. The Bonar score (P = 0.05), and the number of mast cells (P = 0.02) were significantly higher in the runners compared to the controls. Furthermore, SHGM showed focal collagen disorganization in the runners, and reduced collagen density (P = 0.03). IL‐3 mRNA levels were correlated with mast cell number in sedentary animals. The qPCR analysis showed no significant differences between the groups in the other analyzed targets. The current study demonstrates that 7‐week HIUR causes structural changes in the calcaneal tendon, and further that these changes are associated with an increased mast cell density.